Mediating Role of Psychological Inflexibility as Transdiagnostic Factor in the Relationship Between Emotional Dysregulation and Sleep Problems With Symptoms of Emotional Disorders - Orouji, Farrin; Abdi, Reza; Chalabianloo, Gholamreza (Frontiers in Psychology, 2022)
The present study aims to investigate the mediating role of psychological inflexibility as a transdiagnostic factor in the relationship of between emotional dysregulation and sleep problems with symptoms of emotional disorders. A total of 500 subjects were selected by random multi-stages clustering from three universities and they completed Pittsburgh sleep quality index, difficulties in emotional regulation scale, Acceptance and action questionnaire – II, Inventory of depression and anxiety symptoms. The results of correlation coefficients revealed that there is a positive and significant correlation between emotional dysregulation, sleep problems and psychological inflexibility with emotional disorders. In addition, the results showed that that psychological inflexibility acts as transdiagnostic factor which mediates the relationship of emotional dysregulation and sleep problems with symptoms of emotional disorders. The current findings illustrate how emotional dysregulation and sleep problems affect emotional disorders through psychological inflexibility.